Law No. 15 of the Year 2023 Amending Certain Provisions of Law No. 147 of the Year 1984 Imposing the State Financial Resources Development Fee = قانون رقم 15 لسنة 2023 بتعديل بعض أحكام القانون رقم 147 لسنة 1984 بفرض رسم تنمية الموارد المالية للدولية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic